2020
DOI: 10.1007/s10712-020-09604-6
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning from Space for a Few Key Tipping Points in Physical, Biological, and Social-Ecological Systems

Abstract: In this review paper, we explore latest results concerning a few key tipping elements of the Earth system in the ocean, cryosphere, and land realms, namely the Atlantic overturning circulation and the subpolar gyre system, the marine ecosystems, the permafrost, the Greenland and Antarctic ice sheets, and in terrestrial resource use systems. All these different tipping elements share common characteristics related to their nonlinear nature. They can also interact with each other leading to synergies that can le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 249 publications
(326 reference statements)
0
19
0
1
Order By: Relevance
“…The wavelet analysis hints at a recent increase in the overall spectral power of the AMV. The changes in spectral characteristic of a time series can be used as an early warning of regime shift in dynamical systems, as shown in numerous studies [50][51][52] . In particular, the AMOC is well-known as a potential tipping element of the climate system 53 and it has been…”
Section: Unforced Multidecadal Variability and Ongoing Bifurcationmentioning
confidence: 99%
See 3 more Smart Citations
“…The wavelet analysis hints at a recent increase in the overall spectral power of the AMV. The changes in spectral characteristic of a time series can be used as an early warning of regime shift in dynamical systems, as shown in numerous studies [50][51][52] . In particular, the AMOC is well-known as a potential tipping element of the climate system 53 and it has been…”
Section: Unforced Multidecadal Variability and Ongoing Bifurcationmentioning
confidence: 99%
“…shown that an AMOC regime shift in climate models might necessitate the knowledge of hundreds of years of time series of AMOC variations 50,52 , which is prohibitive with direct observations of it at 26°N that only last for less than 20 years 54 . Here, the reconstruction of our AMV as an internal mode of variability can be related to the internal dynamics of the AMOC through its impact on heat transport and the AMV 13,14,55 .…”
Section: Unforced Multidecadal Variability and Ongoing Bifurcationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the development of anthropogenic hazards can enhance or interact with already existing natural risks, thus leading to more complex effects, which in turn are more difficult to predict. Hydro-meteorological hazards such as cyclones, storms, heat waves, floods and droughts are intensifying as time goes on and some of them are becoming more frequent (e.g., heat waves and floods) (Stocker et al 2013;Yamazaki et al 2018 and references therein), and increasing the vulnerability of populations. However, the societal and economic impacts of natural and man-made hazards will differ depending on the geographical region, southern countries paying generally a heavier price in terms of human casualties and goods lost (Hyndman and Hyndman 2016).…”
mentioning
confidence: 99%